The effect of hunger level on predation dynamics in the spider Nesticodes rufipes: a functional response study - Rossi, Marcelo N.; Reigada, Carolina; Godoy, Wesley A. C. (Springer, 2006)
It is well known that a predator has the potential to regulate a prey population only if the predator responds to increases in prey density and inflicts greater mortality rates. Predators may cause such density-dependent mortality depending on the nature of the functional and numerical responses. As spiders are usually faced with a shortage of prey, the killing behavior of the spider Nesticodes rufipes at varying densities of Musca domestica was examined here through laboratory functional response experiments where spiders were deprived of food for 5 (well-fed) or 20 days (hungry). An additional laboratory experiment was also carried out to assess handling time of spiders. The number of prey killed by spiders over 24- and 168-h periods of predator-prey interaction was recorded. Logistic regression analyses revealed the type II functional response for both well-fed and hungry spiders. We found that the lower predation of hungry spiders during the first hours of experimentation was offset later by an increase in predation ( explained by estimated handling times), resulting in similarity of functional response curves for well-fed and hungry spiders. It was also observed that the higher number of prey killed by well-fed spiders over a 24- h period of spider-prey interaction probably occurred due to their greater weights than hungry spiders. We concluded that hungry spiders may be more voracious than well-fed spiders only over longer time periods, since hungry spiders may spend more time handling their first prey items than well-fed spiders.
Keywords: Nesticodes rufipes; Musca domestica; functional response; predator-prey interaction; poultry house; shortage of prey